DAMPAK UPAH MINIMUM TERHADAP TINGKAT PENGANGGURAN TERBUKA DI PROVINSI MALUKU - Diar Muzna Tangke (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2023)
The problem of wages is a classic problem that has not been resolved until now. The government is not only facing the problem of surplus labor or the problem of an increasing workforce, but how to make policies related to the protection and improvement of workers' welfare. Maluku with a population that continues to increase from year to year. BPS noted that in August 2019, Maluku Province was ranked third with the highest unemployment rate nationally. The purpose of this study is to see the impact of drinking wages on the open unemployment rate in Maluku Province. The research method used is a quantitative method with secondary data type time series 2001-2020. The results of the study show that the minimum wage has a negative effect on the Open Unemployment Rate in Maluku province during the period 2001-2020.